Arterial Calcification in Chronic Kidney Disease: Key Roles for Calcium and Phosphate - Shanahan, Catherine M. (2011)
Vascular calcification contributes to the high risk of cardiovascular mortality in chronic kidney disease (CKD) patients. Dysregulation of calcium (Ca) and phosphate (P) metabolism is common in CKD patients, and drives vascular calcification. In this article, we review the physiological regulatory mechanisms for Ca and P homeostasis and the basis for their dysregulation in CKD. In addition, we highlight recent findings indicating that elevated Ca and P have direct effects on vascular smooth muscle cells (VSMCs) that promote vascular calcification, including stimulation of osteo/chondrogenic differentiation, vesicle release, apoptosis, loss of inhibitors, and ECM matrix degradation. These studies suggest a major role for elevated P in promoting osteo/chondrogenic differentiation of VSMC, whereas elevated Ca has a predominant role in promoting VSMC apoptosis and vesicle release. Furthermore, the effects of elevated Ca and P are synergistic providing a major stimulus for vascular calcification in CKD. Unravelling the complex regulatory pathways that mediate the effects of both Ca and P on VSMCs will ultimately provide novel targets and therapies to limit the destructive effects of vascular calcification in CKD patients.